A Design of Hybrid Energy Storage System for Electric Vehicles (International Journal of Innovative Research in Computer Science & Technology, 2022)
Recently, Electronic Vehicles (EVs) have  been attracted substantial responsiveness and so did the  advance in battery equipment. Although the battery  technology has been significantly advanced, the available  batteries do not entirely meet the energy demands of the  Electric vehicle power depletion. This latter aspect is very  important for urban mobility. Although many EVs are previously available in the market. These topologies of EVs  are based on the diverse combination of batteries, fuel cells,  super-capacitor, flywheels, and regenerative braking  systems, which are used as energy sources and energy  storage devices.
Keywords: Hybrid energy storage system; Hybrid energy storage system; Battery Supercapacitor; Electric vehicle; Regenerative braking